2018
DOI: 10.1093/dnares/dsy036
|View full text |Cite
|
Sign up to set email alerts
|

Genome assembly and gene expression in the American black bear provides new insights into the renal response to hibernation

Abstract: The prevalence of chronic kidney disease (CKD) is rising worldwide and 10–15% of the global population currently suffers from CKD and its complications. Given the increasing prevalence of CKD there is an urgent need to find novel treatment options. The American black bear (Ursus americanus) copes with months of lowered kidney function and metabolism during hibernation without the devastating effects on metabolism and other consequences observed in humans. In a biomimetic approach to better understand kidney ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…1 B ). Consistent with previous results, we found that long interspersed nuclear elements (LINEs) represented the largest percentage of repetitive elements in the Ursidae family ( Srivastava et al 2019 ; Zhu et al 2020 ), however, one study reported fewer total repeats in the American black bear ( Ursus americanus ) and a greater number of repeats overall in the giant panda ( Ailuropoda melanoleuca ) ( Srivastava et al 2019 ). Interestingly, while most Ursid species contain a relatively low percent of small RNA repetitive elements, we find expansions of this repetitive element class in the Andean bear ( Tremarctos ornatus ) and the Japanese black bear ( Ursus thibetanus japonicus ) ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…1 B ). Consistent with previous results, we found that long interspersed nuclear elements (LINEs) represented the largest percentage of repetitive elements in the Ursidae family ( Srivastava et al 2019 ; Zhu et al 2020 ), however, one study reported fewer total repeats in the American black bear ( Ursus americanus ) and a greater number of repeats overall in the giant panda ( Ailuropoda melanoleuca ) ( Srivastava et al 2019 ). Interestingly, while most Ursid species contain a relatively low percent of small RNA repetitive elements, we find expansions of this repetitive element class in the Andean bear ( Tremarctos ornatus ) and the Japanese black bear ( Ursus thibetanus japonicus ) ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…Chromosome or scaffold-level assemblies of the following species were used for this study: Neofelis nebulosa , clouded leopard; Panthera pardus , leopard ( 46 ); Panthera tigris , tiger ( 47 ); Acinonyx jubatus, cheetah ( 48 ); Puma concolor, puma ( https://www.ncbi.nlm.nih.gov/nuccore/QAVW00000000.1 ); Canis lupus dingo , dingo ( https://www.ncbi.nlm.nih.gov/nuccore/QKWQ00000000.1 ); Lycaon pictus , African wild dog ( 49 ); Vulpes vulpes , red fox ( 50 ); Ursus americanus , black bear ( 51 ); and Ursus arctos , grizzly bear ( 52 ); Ursus maritimus , polar bear ( 53 ) ( Dataset S1 ). All assemblies were obtained from the DNA Zoo database ( https://www.dnazoo.org/assemblies , cutoff date, July 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The gene sets from nine species-human, mouse, dog, giant panda, polar bear, tiger (Panthera tigris, GCF_000464555.1) 6 , brown bear (Ursus arctos, GCF_003584765.1) 7 , American black bear (Ursus americanus, GCA_003344425.1) 8 (Srivastava et al, 2019), and Tibetan black bear-were used for gene clustering. We identified clusters for all protein-coding genes using OrthoFinder v2.3.4 (Emms and Kelly, 2015) with default parameters.…”
Section: Reconstruction Of Phylogenetic Relationshipsmentioning
confidence: 99%